The Resistance of Vibrio cholerae O1 El Tor Strains to the Typing Phage 919TP, a Member of K139 Phage Family - Shen, Xiaona; Zhang, Jingyun; Xu, Jialiang; Du, Pengcheng; Pang, Bo; Li, Jie; Kan, Biao (Frontiers in Microbiology, 2016)
Bacteriophage 919TP is a temperate phage of Vibrio cholerae serogroup O1 El Tor and is used as a subtyping phage in the phage-biotyping scheme in cholera surveillance in China. In this study, sequencing of the 919TP genome showed that it belonged to the Vibrio phage K139 family. The mechanisms conferring resistance to 919TP infection of El Tor strains were explored to help understand the subtyping basis of phage 919TP and mutations related to 919TP resistance. Among the test strains resistant to phage 919TP, most contained the temperate 919TP phage genome, which facilitated superinfection exclusion to 919TP. Our data suggested that this immunity to Vibrio phage 919TP occurred after absorption of the phage onto the bacteria. Other strains contained LPS receptor synthesis gene mutations that disable adsorption of phage 919TP. Several strains resistant to 919TP infection possessed unknown resistance mechanisms, since they did not contain LPS receptor mutations or temperate K139 phage genome. Further research is required to elucidate the phage infection steps involved in the resistance of these strains to phage infection.